Effect of whitening dentifrices containing optical agent on the variation of color, roughness and mass of a nanoparticulate composite resin - OLIVEIRA,Rafaela Silva (2020)
Abstract Introduction Blue covarine is a pigment that promotes optical changes in dental surfaces, providing whitening. Objective To evaluate in vitro the effect of bleaching dentifrices containing Blue covarine in nanoparticulate composite resin subjected to artificial darkening. Material and method One hundred sixty (160) specimens (PBs) of FILTEK Z350XT nanoparticulate composite resin were randomly divided into two experiments: Experiment I - 8 groups (n=10) submitted to brushing with an electric toothbrush for 1 month; Experiment II - 8 groups (n=10) submitted to simulated brushing for 6, 12 and 24 months. Groups were distributed according to the solution/dentifrice tested: CG (distilled water) and 7 test groups (GT1- Coltene Herjos, GT2- Colgate Total 12 Clean Mint, GT3- Colgate Luminous White Brilliant Mint, GT4- Oral B 3D White Perfection, GT5- Close Up White Now Glacier Fresh, GT6- Close Up White Attraction Diamond and GT7- Sorriso Xtreme White Evolution). Result In Experiment I, there was greater ∆E in GT6 in relation to CG, GT2, GT4 and GT5, with no differences among them. In Experiment II, after 24 months of brushing, there was greater ∆E in groups GT6 and GT7. After 24 months of simulated brushing, there was no change in roughness or loss of mass in any group. Conclusion The whitening effect promoted by dentifrices containing the agent Blue covarine seems to be related to the association of this agent with the abrasives present in the formulations of whitening dentifrices.